The Influence Of Work Supervision, Work Culture And Work Environment On Employee Productivity PT ABC - Yuningsih, Nining; Wiryawan, Tri Wahyu; Kosim, Muhammad; Purnamasari, Pupung (Entrepreneurship Faculty, Universitas Garut, 2023)
Human resource management plays a very important role for the company in order to provide maximum results besides that it will also have the best professionalism that can be relied upon to achieve the company's goals and objectives, namely getting maximum profit. The purpose of this research is to analyze the effect of work supervision, work culture, and work environment on employee productivity at PT ABC. The company has goals to be achieved, and it is desirable that workers want to work according to the standards set by the company, and the company wants its employees to work very productively. The sample in this study were 70 respondents. This research uses quantitative methods using validity tests, reliability tests, multicollinearity tests, heteroscedasticity tests multiple regression tests, t tests and F tests with the help of SPSS statistics.Keywords: Work Supervision, Work Culture, Work Environment and Work Productivity